Anthropometric characteristics and physical condition of active older adults from the municipality of Armenia, Colombia 2022 - García-Cardona, Diana María; Toro-López, Marisel; Ramírez, Mónica Alexandra; Sánchez-Muñoz, Oscar Eduardo; Cadena, Andrés Felipe; Ramírez-Gutiérrez, Julián; Cardona, Marta (Universidad y Salud, 2023)
Introduction: Changes in body composition in aging populations are associated with their health and functionality. Objective: To determine the anthropometric characteristics and physical condition of physically active older adults from the city of Armenia. Materials and methods: A descriptive cross-sectional study. The assessment of the body composition was conducted following the guidelines of the International Society for the Advancement in Kinanthropometry. The Senior Fitness Test (SFT) battery was used to evaluate physical condition. Results: 468 older adults were evaluated. The mean height and body mass were 1.57 m and 69.46 kg for women, respectively, while the mean values for male participants were 1.67 m and 78.29 kg. Female older adults had higher percentages of adipose tissue respect to muscle tissue, whereas male participants showed the opposite pattern. Finally, physical condition was below the normal reference range of the SFT battery. Conclusion: In general terms, older adults were overweight. Based on the WHO guidelines and the various analyzed indicators (waist-hip ratio, muscle mass index, abdominal circumference, among others), older adults are at a moderate-high risk to suffer chronic non-communicable diseases.